ANALISIS KEMAMPUAN KEUANGAN DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH KOTA PEKANBARU (2010 – 2014) - Putri Nia Desita; Kirmizi -; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The ability of local governments in managing finances is reflected toward Budget revenue and expenditure which describes the ability of local goverments in financing implementation of the development activity, as well as equity and justice by developing the whole potential of each region. Formulation of the research is: is there a regional financial development capability in Pekanbaru city in order to support the implementation of regional autonomy? Then, the purpose of this study is to determine the development of the city’s financial ability of Pekanbarucity in fiscal 2010 – 2014 in order to support the implementation of regional autonomy. This study is a descriptive comparative study with the object of study is Financial Management Board and the Regional Asset pekanbaru city. Secondary data is needed is the realization of the reflected toward budget revenue and expenditure in 2010 – 2014. Methodology of data collection used in this study written or documentation. Analysis of the data used: 1. The independence ratio of the financial area, 2. The decentralization ratio of the fiscal degree, 3. The index of ratio routin capability, 4. The accord of ratio, 5. The growth of ratio. The result showed: 1. The independence ratio of the financial area is insturctive pattern, 2. The degree of fiscal decentralization are at less intervals that is 17,68%. 3. Ratio routine capability index is less scale that is 37,01%. 4. The accord of ratio showed the result of routine expenditure is greater than the development expenditure amounted to 47,16% and 40,70% of development expenditure. 5. Finally, the growth occured in positive growth.Keywords: the capacity of local financial, regional autonomy